Extrapolated cyclic subgradient projection methods for the convex feasibility problems and their numerical behaviour. (2nd January 2019) - Cegielski, Andrzej; Nimana, Nimit
ABSTRACT: We present two versions of the extrapolated cyclic subgradient projections method for solving the convex feasibility problem. Moreover, we present the results of numerical tests, where we compare the methods with the classical cyclic subgradient projections method.